DETERMINAN NILAI PERUSAHAAN PUBLIK MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI 2015-2019 - Adityaputra, Stephanus Andi; Ariyanto, Stefanus (Ultimaccounting Jurnal Ilmu Akuntansi, 2020)
This research examines several determinants that may have effect to firm value of the consumer goods manufacturing sector in Indonesia in 2015-2018, proxied with Price to Book Value (PBV). The factors that are thought to to have effect against firm value are Price Earning Ratio (PER) which shows potential future profits and investment choices, financial leverage (DER) which reflects the comparison between source of firm's funding, Dividend Payout Ratio (DPR) which is a factor that attracts investor interest, and Return on Equity (ROE) which reflects the ability of the firm to generate net income from its equity. This research is important because firm value is a reflection of the shareholder's welfare. The study reveals that DER negatively and significantly influence the PBV, as well as significant effect of all other independent variables simultaneously on PBV. Keywords: Firm Value, financial leverage, Dividend Payout Ratio, Price Earning Ratio, Return On Equity.